Sulfur mustard causes oxidative stress and depletion of antioxidants in muscles, livers, and kidneys of Wistar rats - Pohanka, Miroslav; Stetina, Rudolf; Svobodova, Hana; Ruttkay-Nedecky, Branislav; Jilkova, Martina; Sochor, Jiri; Sobotka, Jakub; Adam, Vojtech; Kizek, Rene (Drug and chemical toxicology, 2013)
Sulfur mustard (SM) is a chemical warfare agent with cytotoxic effect and a tight link to oxidative stress (OS). Depletion of antioxidants is considered as a cause of detrimental consequence and belongs to the important steps leading to cell death. The oxidative injury appearing after SM exposure is not well understood. Nevertheless, identification of the pathological processes would be a good opportunity to establish an efficient therapy. Here, we focused our effort on an estimation of reactive oxygen species homeostasis and apoptotic processes in Wistar rats exposed to 0-160 mg/kg of SM. We assayed antioxidant activity, thiobarbituric acid reactive substances, reduced glutathione/oxidized glutathione, metallothionein, glutathione reductase, glutathione peroxidase, glutathione S-transferase, caspase 3, and glucose in the livers, kidneys, and muscles of the animals. Significant OS, depletion of low-molecular-mass antioxidants, increase in caspase activity, and some other processes related to SM action were determined. Moreover, we infer a principal role of OS in the tested organs.
Keywords: Male; Rats, Wistar; kosterní svaly; látky reagující s kyselinou thiobarbiturovou; Oxidative Stress; Animals; potkani Wistar; Thiobarbituric Acid Reactive Substances; yperit; antioxidancia; Chemical Warfare Agents; mužské pohlaví; glutathion; krysa rodu Rattus; Kidney; oxidační stres; Muscle, Skeletal; Oxidoreductases; Antioxidants; Rats; chemické bojové látky; Liver; zvířata; Glutathione; ledviny; Mustard Gas; játra; oxidoreduktasy